2020
DOI: 10.1002/aoc.5574
|View full text |Cite
|
Sign up to set email alerts
|

Green biosynthesis of gold nanoparticles using Croton sparsiflorus leaves extract and evaluation of UV protection, antibacterial and anticancer applications

Abstract: Our study reports greener synthesis of gold nanoparticles (AuNPs) tethered to the extract of Croton sparsiflorus and in vitro evaluation of UV‐protection, antibacterial and anticancer activities. Sophisticated instrumental analytical techniques such as UV–vis spectrophotometer, FT‐IR, XRD, FE‐SEM, and TEM were employed for the existence and confirmation of the nanoparticles. FT‐IR and HPLC analysis were executed in the identification of the plausible functional groups implicated in the reduction of gold ions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 83 publications
1
20
0
1
Order By: Relevance
“…Sun et al [21] stated that the SAED pattern showed the presence of bright circular pattern rings implying that AuNPs were of a crystalline nature. Much similar to the present report, Boomi et al [54] has reported the XRD patterns depicting four distinct peaks 38.21 , 44.39 , 64.62 , and 77.59 corresponding to (111), (200), (220), and (311) planes indicating fcc nature of gold nanoparticles synthesized using Croton sparsiflorus leaves extract.…”
Section: Physicochemical Characterization Of Pa-aunpssupporting
confidence: 90%
“…Sun et al [21] stated that the SAED pattern showed the presence of bright circular pattern rings implying that AuNPs were of a crystalline nature. Much similar to the present report, Boomi et al [54] has reported the XRD patterns depicting four distinct peaks 38.21 , 44.39 , 64.62 , and 77.59 corresponding to (111), (200), (220), and (311) planes indicating fcc nature of gold nanoparticles synthesized using Croton sparsiflorus leaves extract.…”
Section: Physicochemical Characterization Of Pa-aunpssupporting
confidence: 90%
“…The reaction was monitored by UV-visible spectrophotometer till the end of 1 h, and the perfect sharp band was observed at 552 nm, which was attributable to SPR of AuNPs (curve B). 44 The formation of the SPR band may be due to the shape and size during the production of AuNPs 58,59 which can be further confirmed by the formation of spherical and rod-like shapes of AuNPs. This may be due to the attainment of saturation in the bio-reduction of Au 3+ .…”
Section: Uv-vis Analysismentioning
confidence: 86%
“…The particle size obtained through XRD analysis is further corroborated by the particle size determined from the HR-TEM. 44.…”
Section: Xrd Analysismentioning
confidence: 99%
See 2 more Smart Citations